Mortality and fertility: impact evaluation of BRAC reproductive health and disease control programme - Karim, Fazlul; Gani, Md. Showkat; Tripura, Abhilash (BRAC Research and Evaluation Division (RED), 2019)
This study assessed the impact of BRAC's RHDC programme on fertility and mortality compared to the baseline status as well as the comparison area. Subsequently, a number of variables such as total fertility rate (TFR), age-specific fertility rates (ASFR), crude birth rate (CBR), crude death rate (CDR), infant mortality rate (IMR), child mortality rate (CMR), under-five mortality rate (USMR) and age-specific death rates (ASDR) were chosen for analysis. These variables are measurable and widely accepted to reveal the impact of any reproductive health programme. Moreover, we have baseline data on these variables for comparison. In the baseline study (1992) fertility and mortality data were collected from 12,073 households (programme 8,072 and comparison 4,001) representing a total of 261 villages (programme 184 and comparison 77). But, in the follow-up study done in 2000, 103 villages (programme 80 and comparison 23) were revisited. Using the cluster survey method, data were collected from 8,033 households (programme 4,003 and comparison 4,030) in the follow-up study. Each married woman was asked to provide information on the number of children she had given birth during the 12 months recall period. Information on all the live births were collected, such as name, sex, date and place of birth, age, father's name and occupation, and birth order of the child. Similarly, data on death that occurred during the last 12 months along with name, sex, month and year of death, age at death, marital status and causes of death, were also collected. The study found that the reduction of TFR from the baseline to the follow-up study was sharper in the programme area than in the comparison (21% versus 13%). The present TFR for both the areas was identical (programme 2.7 and comparison 2.6/1,000 women). It is to be noted that the benchmark TFR was higher in the programme area than in the comparison area (3.4 versus 3.0).